Fungal Root Microbiome from Healthy and Brittle Leaf Diseased Date Palm Trees (Phoenix dactylifera L.) Reveals a Hidden Untapped Arsenal of Antibacterial and Broad Spectrum Antifungal Secondary Metabolites - Mefteh, Fedia B.; Daoud, Amal; Chenari Bouket, Ali; Alenezi, Faizah N.; Luptakova, Lenka; Rateb, Mostafa E.; Kadri, Adel; Gharsallah, Neji; Belbahri, Lassaad (Frontiers in Microbiology, 2017)
In this study, we aimed to explore and compare the composition, metabolic diversity and antimicrobial potential of endophytic fungi colonizing internal tissues of healthy and brittle leaf diseased (BLD) date palm trees (Phoenix dactylifera L.) widely cultivated in arid zones of Tunisia. A total of 52 endophytic fungi were isolated from healthy and BLD roots of date palm trees, identified based on ITS-rDNA sequence analysis and shown to represent 13 species belonging to five genera. About 36.8% of isolates were shared between healthy and diseased root fungal microbiomes, whereas 18.4% and 44.7% of isolates were specific to healthy and BLD root fungal microbiomes, respectively. All isolates were able to produce at least two of the screened enzymes including amylase, cellulase, chitinase, pectinase, protease, laccase and lipase. A preliminary screening of the isolates using disc diffusion method for antibacterial activity against four Gram-positive and three Gram-negative bacteria and antifungal activities against three phytopathogenic fungi indicated that healthy and BLD root fungal microbiomes displayed interesting bioactivities against examined bacteria and broad spectrum bioactivity against fungal pathogens. Some of these endophytic fungi (17 isolates) were fermented and their extracts were evaluated for antimicrobial potential against bacterial and fungal isolates. Results revealed that fungal extracts exhibited antibacterial activities and were responsible for approximately half of antifungal activities against living fungi. These results suggest a strong link between fungal bioactivities and their secondary metabolite arsenal. EtOAc extracts of Geotrichum candidum and Thielaviopsis punctulata originating from BLD microbiome gave best results against Micrococcus luteus and Bacillus subtilis with minimum inhibitory concentration (MIC, 0.78 mg/mL) and minimum bactericidal concentration (MBC, 6.25 mg/mL). Geotrichum candidum gave the best result against Rhizoctonia solani with MIC 0.78 mg/mL and minimum fungicidal concentration (MFC, 6.25 mg/mL). In conclusion, using plant microbiomes subjected to biotic stresses offers new endophytes with different bioactivities than those of healthy plants. Therefore, date palm endophytic fungi represent a hidden untapped arsenal of antibacterial and broad spectrum antifungal secondary metabolites and could be considered promising source of bioactive compounds with industrial and pharmaceutical applications.